Safety and health inspection checklist iOS application / Affira Mastika Abdul Azid - Abdul Azid, Affira Mastika (2014)
This thesis presents the safety and health inspection checklist iOS application. Industrial safety officer usually face the problem of inefficient safety inspection procedure due to the hassle of completing a conventional checklist form. This often hinders a seamless inspection reporting and analyzing process from being carried out. The safety and health inspection checklist is fully developed using Xcode SDK. The development of the project reached the target of building a user log in function with create new account feature, a table with 14 categories of the respective area of concern in safety and the details option for the each of the inspection process. Using this application, user or safety officer can simply select the inspection specific concern, complete the inspection details, and finally save the inspection report on the device for further reference. As using this application is much more efficient and less time-consuming for the inspection purpose, user or safety officer can now spend more of their precious time for other urgent matter regarding safety and health.